2020
DOI: 10.1055/a-1121-7851
|View full text |Cite
|
Sign up to set email alerts
|

Human Skeletal Muscle Mitochondrial Adaptations Following Resistance Exercise Training

Abstract: It is universally accepted that resistance training promotes increases in muscle strength and hypertrophy in younger and older populations. Although less investigated, studies largely suggest resistance training results in lower skeletal muscle mitochondrial volume; a phenomenon which has been described as a “dilution of the mitochondrial volume” via resistance training. While this phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 96 publications
6
57
0
Order By: Relevance
“…Resistance training has been well recognized as an effective method to increase muscle hypertrophy and strength (Folland & Williams, 2007). However, whether or not RT induces mitochondrial adaptations remains equivocal and poorly investigated, especially in older individuals (Parry et al, 2020). We investigated the acute and chronic effects of RT on markers of mitochondrial content and remodeling in older individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance training has been well recognized as an effective method to increase muscle hypertrophy and strength (Folland & Williams, 2007). However, whether or not RT induces mitochondrial adaptations remains equivocal and poorly investigated, especially in older individuals (Parry et al, 2020). We investigated the acute and chronic effects of RT on markers of mitochondrial content and remodeling in older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a growing body of literature investigating the mitochondrial adaptations to RT in both younger (Alvehus, Boman, Söderlund, Svensson, & Burén, 2014;Lim et al, 2019;Porter, Reidy, Bhattarai, Sidossis, & Rasmussen, 2015) and older (Flack et al, 2016;Manfredi et al, 2013;Miller et al, 2020;Zampieri et al, 2016) participants, with mixed results. As pointed out by Parry, Roberts, & Kavazis (2020), RT may impose a sufficient energetic stimulus to promote mitochondrial adaptations in older participants. Although there is a growing interest in the effects of RT on mitochondrial biogenesis in older participants, there is a paucity of research investigating its effects on markers of mitochondrial remodeling, which is essential for quantity and quality control of the mitochondrial network.…”
mentioning
confidence: 99%
“…To this end, several resistance training studies have reported that mitochondrial density remains unaltered [28][29][30] or decreases [31][32][33][34][35], and fewer studies have shown resistance training increases mitochondrial density [36]. We recently posited that, while most of the literature indicates mitochondrial density is not affected in younger individuals, resistance training may facilitate this adaption in older and more sedentary individuals due to increased metabolic demand [37]. However, we did not previously speculate that resistance training-induced increases in muscle NAD + concentrations were responsible for this adaptation.…”
Section: Agingmentioning
confidence: 99%
“…It was demonstrated that resistance training may promote ameliorations in walking endurance, muscle oxidative capacity and strength [ 275 , 276 , 277 ]. In aged people, the benefits of resistance exercise on muscle function were recently attributed to improvement of mitochondrial function, muscle hypertrophy, modulation of myonuclear domain, and newly formed myonuclei, increases of satellite cell-capillary interaction and content [ 49 , 278 , 279 ]. Of note, it appears that Nordic walking also improves lower limb strength, aerobic aptitude, body composition, life, and sleep quality in old people [ 280 ].…”
Section: Impact Of Exercise Training and Practical Recommendationsmentioning
confidence: 99%